Tackling Nitrosomonas europaea culture problems for future applications in inshore aquaculture - Padrão, Jorge (2016)
Worldwide aquaculture production represents nearly 160 million tonnes per year, roughly the double of captured fish. Technological improvements are required to provide and improve sustainability to the constant aquaculture production growth. Inshore aquaculture reduces dramatically the risk of infection of the cultured organisms, as sea water is treated before use. Contrariwise, to prevent the increase of operational costs, water must be recirculated multiple times. The high cumulative load of ammonium produced during the fish metabolism requires an especially efficient water treatment, namely for the denitrification process, which usually relies on biological consortium processes to be cost-efficient. Thus, nitrifying and denitrifying microorganisms must be further studied and their production scaled up in order to allow the development of novel technologies and fulfil the increasing demand of denitrification units. Nitrosomonas europaea is the most extensively studied ammonia oxidizing bacteria, being a ubiquitous nitrification organism. Its vital role in the nitrogen cycle is however impaired by the limited energy achieved by this inefficient source of energy, which is partially dedicated to fixate carbon from gaseous carbon dioxide, restricting biomass production. For scale up purposes the design of a culture medium with no precipitation of its constituents is essential, since inorganic debris may significantly impair downstream processing. Moreover, a non-precipitating medium allows a maximum bioavailability of all elements present in its recipe and improves recirculation effectiveness. A new formulation for N. europaea culturing was studied and optimized, fulfilling the addressed objective. This formulation was further tested using moderate pressure displaying positive results in biomass output. The higher N. europaea cell concentration allowed an immobilization in a latex based biocoating, which was evaluated for a possible denitrifying cartridge application.